The effect of replacing standard carburetor with PE-28 carburetor on performance fuel consumption on 2006 Honda Tiger Revo - I Nengah Ludra Antara; I Nyoman Sutarna; Ida Bagus Puspa Indra (Journal of Applied Mechanical Engineering and Green Technology, 2021)
Carburetors are one of the important components on motorcycles, through modification of replacing Standard Carburetor with Racing Carburetor is one of the ways to improve engine performance. There are several types and sizes of PE, namely PE 24, PE 28, PE 38. PE 28 carburetor is often used on racing motorbikes, both Drag bikes and Roodrace bikes, where this carburetor is able to produce maximum engine performance. By testing the maximum power using a standard carburetor found at 7000 rpm engine speed, which is 11.3 HP, while the maximum power testing using a PE 28 carburetor is found at 7000 rpm engine speed, which is 11.7 HP. For testing the maximum torque using a standard carburetor found at 6000 rpm engine speed, which is 11.7 N.m, while the maximum torque testing using a PE 28 carburetor is found at 7000 rpm engine speed, which is 11.8 N.m. The use of PE 28 carburetor on a 4 stroke motorcycle greatly affects the amount of fuel consumption, it is because the PE 28 carburetor is a racing carburetor that is very suitable for those who want top speed. In addition, the advantage of the PE 28 carburetor is that it is able to improve engine performance because the type of carburetor is different from the standard and there are changes in the dimensions of the venturi hole and intake manifold, so that it can fog up more air and fuel to be brought into the combustion chamber or into the engine cylinder.